Differentiation of Salmonella enteritidis phage type 8 strains: evaluation of three additional phage typing systems, plasmid profiles, antibiotic susceptibility patterns, and biotyping. - Stubbs, A D (1994)
Three additional phage typing systems for Salmonella enteritidis, plasmid analysis, biochemical tests, and antimicrobial susceptibility tests, were used in an attempt to subdivide 30 phage type 8 (phage typing system used by the WHO International Center for Enteric Phage Typing, London, England) isolates. These isolates represented 18 different egg-related outbreaks (21 strains) and 9 reference strains or strains that were not egg-associated. Only 7 of the 30 strains (28%) were subdivided by one or more of the methods used; this included 3 of the 21 strains from egg-related outbreaks. Twenty-seven strains contained a 55-kb plasmid that is associated with S. enteritidis. Of 65 additional phages tested, 2 from the phage typing system obtained from the Pasteur Institute, Paris, France, were useful in differentiating the three strains that lacked the 55-kb plasmid. Although the results obtained for the 21 strains from egg-related outbreaks showed that the strains had minor phenotypic differences, the overall results suggested that the strains may represent a single clone. Studies are planned to test additional phages and other typing methods to see whether strains of phage type 8 can be further differentiated.